Business and innovative development as the basis of the policy of economic recovery of Ukraine - Ivanova , Tetiana (Ways to Improve Construction Efficiency, 2025)
The article examines the role of innovation as a key factor in the recovery and sustainable development of the Ukrainian economy in the face of military challenges and post-war transformation. The current state of the national economy is characterized by significant losses of production potential, destruction of infrastructure, reduction of economic activity and requires the formation of a new development model focused on innovation, investment and development of intellectual capital. The impact of a full-scale war on the functioning of business, the state of key sectors of the economy, as well as the dynamics of macroeconomic indicators is analyzed. It is established that despite significant losses, the business sector demonstrates the ability to adapt through digitalization, relocation of production and diversification of sales markets. The article summarizes current challenges, including disruption of logistical connections, shortage of financial resources, reduced investment attractiveness, and increased institutional risks. Particular attention is paid to international initiatives for the recovery of Ukraine, in particular the formation of strategic approaches to economic reconstruction and attracting financial assistance. The role of the state in creating a favorable institutional environment is determined, including anti-corruption policy, deregulation, support for small and medium-sized businesses, and the development of financing mechanisms. Effective interaction between the state, business, and international partners is a necessary condition for successful recovery. The article identifies priority areas for innovative transformation of the economy, including the development of high-tech production, information technologies, the agro-industrial sector, and the defense-industrial complex. The need to create innovation clusters, industrial parks, and intensify research and development activities is emphasized. The implementation of innovative approaches based on the development of intellectual capital and entrepreneurial activity will contribute to increasing the competitiveness of the national economy, increasing export potential and forming a new economic structure. The post-war recovery of Ukraine should be based on the principles of sustainable development, digitalization and integration into the European economic space. The results of the study can be used to develop state economic policy and strategies for the recovery of the national economy.